The Phytoremediation effect on the pH and TSS of acid mine drainage by constructed wetland metods - Christine Elia Benedicta; Kemala Hadidjah; Andi Gita Tenri Sumpala; Rahmad Hidayat Pradana (Politeknik Pertanian Negeri Samarinda, 2025)
Coal mining is a significant contributor to the economy of East Kalimantan Province, with most activities employing open-pit mining systems involving stripping and transporting soil surface. If not properly managed, these activities can lead to Acid Mine Drainage (AMD), which is rainwater and groundwater reacting with sulfide content. Without any treatment before discharge into the environment, AMD can cause environmental pollution. One such treatment method is constructed wetlands, utilizing Pontederia crassipes to absorb heavy metals present in AMD. This study aims to determine the phytoremediation effect on the pH and TSS of acid mine drainage using constructed wetland methods. The research was conducted at PT. Lanna Harita Indonesia, using three 60x50x50 cm container boxes as a collection pond for AMD, a phytoremediation pond containing sand, zeolite rock, and filter cotton, and a constructed wetland phytoremediation pond containing Pontederia crassipes. The results show that Pontederia crassipes can increase the acidic pH from 4.11 to 7.65 and reduce the TSS value from 1016 mg/L to 22 mg/L. This indicates that the final AMD values after phytoremediation treatment comply with the quality standards outlined in East Kalimantan Regional Regulation No. 2 of 2011, meaning it is suitable for discharge into the environment with minimal negative environmental impact.